Improving neuroplasticity and Quality of Life in children with Cerebral Palsy: a customized intensive motor training protocol integrating the HABIT-ILE approach - Vacchini, Valeria; Brafa, Benedetta; Nicotra, Roberta; Capelli, Elena; Signorini, Sabrina; Gasparroni, Verusca; Michelutti, Arianna; Oldrati, Viola; Galli, Jessica; Urgesi, Cosimo; Cattaneo, Zaira; Fazzi, Elisa Maria; et al. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionCerebral Palsy (CP) refers to a heterogeneous group of disorders resulting from early brain injury during development. The clinical and functional consequences are variable, but primarily characterized by motor and postural deficits that limit independence in activities of daily living, impacting child's and family's quality of life. There is consensus on the effectiveness of rehabilitative interventions when started early and administered intensively, leveraging neuronal plasticity. The Hand-Arm Bimanual Intensive Training Including Lower Extremities (HABIT-ILE) rehabilitation approach was developed to improve motor skills in children with CP, focusing on bimanual activities with integration of the lower limbs. The aim of this study is to present an intensive, individualized motor training protocol, based on HABIT-ILE principles, tailored for children and adolescents with CP.MethodsTo develop the protocol, we conducted a review of literature on HABIT-ILE applications. Additionally, we carried out multidisciplinary focus groups with professionals from three Italian Centers. These discussions focused on therapeutic setting, identifying materials, structuring play activities, to define strategies to enhance applicability and impact of the protocol.ResultsAn intensive intervention protocol based on HABIT-ILE was developed. It consists of 30 h over 10 consecutive days, with daily sessions of 3 h. The intervention, structured around bimanual activities and lower limb involvement, was personalized according to clinical and motivational profile and conceived to be administered in pairs to children aged 6–17 years with CP and upper limb asymmetry. Sessions are divided into three components: bimanual tasks, occupational activities, and gross-motor activities, ensuring a global approach and enhancing neuroplasticity. Daily activities are selected by patients from a predetermined pool chosen by therapists, based on individual profiles and adapted progressively.DiscussionThe HABIT-ILE model represents an intensive and individualized approach for improving motor abilities in these patients. Our protocol, including personalization in an ecological context and pairwork, could increase motivation, adherence, and ultimately therapy effectiveness. We plan to verify feasibility, clinical effectiveness and sustainability of this model in multicenter contexts. Ongoing trials will provide evidence of applicability and efficacy, combined with non-invasive brain stimulation (NIBS) techniques such as transcutaneous vagus nerve stimulation or transcranial alternating current stimulation.Clinical Trial RegistrationClinicalTrials.gov, Identifiers NCT06372028 and NCT06372041.